(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is devoted to the study of the phenomenon of ekphrasis in the works of Donna Tartt, especially in her first novel “The Secret Story”. Ekphrasis as a feature of ancient literature has become an interesting topic for research in modern literary criticism, since in the realities of postmodernism, references and allusions to classical painting are a very common occurrence. The article provides numerous examples from Donna Tartt’s novel, which mentions works of art by Van Gogh, Rubens, Monet and other artists.